A First Description of Arabic on The South Coast of Iran: The Arabic Dialect of Bandar Moqām, Hormozgan. (20th February 2021) - Leitner, Bettina; Anonby, Erik; Taheri-Ardali, Mortaza; Zarka, Dina El; Moqami, Ali
Abstract: Arabic has been spoken as a mother tongue in Iran since pre-Islamic times, but a number of the Arabic dialect groups scattered across the country have not been documented. In this study, we provide a first account of Arabic on Iran's southern coast, with a description of the dialect of Bandar Moqām in western Hormozgan Province. Using the Atlas of the Languages of Iran (ALI) linguistic data questionnaire as well as supplementary elicitation and oral texts, we have documented salient elements of its lexicon, phonology and morphosyntax. Our analysis confirms that Bandar Moqām Arabic fits into the wider Gulf Arabic dialect area, yet is internally heterogenous. On the one hand, it shares many features with the regionally dominant 'Bedouin' type Gulf Arabic koine, but it also aligns with distinctive structures—both retentions and innovations—in the more ancient 'Sedentary' Gulf dialects that originated in southern Arabia. Further, it exhibits a series of structures in common with Mesopotamian Arabic and its descendants that reached as far as Central Asia during the Arab con-quest of greater Persia and are still spoken there today.